51 General practitioners', nurses' and pharmacists' perceptions of psychotropic monitoring in australian aged care facilities. (4th December 2019) - Langford, Aili; Ngo, Garzee Tracey; Chen, Timothy; Roberts, Chris; Schneider, Carl
Abstract : Objectives: Current evidence suggests that Aged Care Facility (ACF) residents are overtreated with psychotropics, with modest benefits of psychotropic use in the geriatric population outweighed by associated morbidity and mortality. Long term psychotropic treatment for behavioural and psychological symptoms of dementia is common despite a lack of evidence of efficacy and demonstrated harms. Psychotropic monitoring by Health Care Professionals (HCPs) may be a valuable mechanism in reducing overtreatment with psychotropics. The extent to which psychotropic monitoring occurs in ACFs and influencing factors are not well established. This study aimed to explore psychotropic monitoring from the perspective of general practitioners' (GPs), registered nurses and accredited pharmacists. Methods: A purposive sample of 31 HCPs working in ACFs was recruited. Semi-structured interviews were conducted with 9 GPs, 12 nurses and 10 pharmacists. A range of questions assessing perceptions of monitoring, facilitators, barriers and proposed solutions were included. Interviews were transcribed verbatim and analyzed through an inductive coding approach using NVivo 11 software. Results: Monitoring was revealed as a multi-faceted concept, influenced by factors at the individual, group, organization and system level. Thematic analysis revealed 6 key themes pertinent to psychotropic monitoring in ACFs: (i) Beliefs and attitudes, (ii) Capability, (iii) Opportunity, (iv) Communication, (v) Guidance and (vi) Regulation. Eighteen further sub-themes were elicited and explored. GPs, pharmacists and nurses conceptualized monitoring differently with GPs and pharmacists describing monitoring as a planned and intermittent activity and nurses depicting monitoring as a passive and continuous aspect of the daily care routine. An inertia of the medication management cycle was identified by participants and a tension between HCPs opportunity and capability to monitor was revealed. The involvement of patients in medication monitoring was not a focus of participant responses revealing that a patient centered approach to monitoring was lacking. All HCPs felt psychotropic monitoring in ACFs was suboptimal and recognized a need for improvements in practices. Conclusion: HCPs play an integral role in psychotropic monitoring and are instrumental to the success of initiatives to improve practices. Variability in HCPs' beliefs and attitudes as well as organizational culture should be considered when designing implementation strategies for interventions to ameliorate suboptimal monitoring practices and reduce overtreatment with psychotropics in ACFs.